Luminography – an Alternative Assay for Detection of von Willebrand Factor Multimers - Schneppenheim, R; Plendl, H; Budde, U (Thrombosis and Haemostasis, 1988)
A luminescence assay was adapted for detection of von Willebrand factor multimers subsequent to SDS-agarose gel electrophoresis and electroblotting onto nitrocellulose. The method is as fast as chromogenic detection methods and appears to be as sensitive as autoradiography without the disadvantages of the latter.
Keywords: Von Willebrand factor (vWF); Multimers; Immunoblotting; Peroxidase-linked antibodies; Luminography